The Influence Of Work Environmet and Motivation On The Performance Of Employees At The Regional Secretariat Of Souht Bengkulu Regency - Royanti Royanti; Tito Irwanto; Siti Hanila (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
HR always plays an active and dominant role in every organizational activity, because humans are the planners, actors and determinants of the realization of organizational goals. Work Environment and Motivation are important because with a Work Environment and Motivation every employee will want to work hard and enthusiastically to achieve higher performance. The research objective was to determine whether there was an influence of the Work Environment and Motivation on employee performance at the Regional Secretariat of South Bengkulu Regency. This type of research used quantitative research. The quantitative approach is a research method based on the philosophy of potivism, used to examine certain populations or samples. The population in this study were all ASN employees at the Regional Secretariat of South Bengkulu Regency, totaling 112 ASN employees. The results of the multiple linear regression analysis Y = 9.378 + 0.373 X1 + 0.421 X2 this illustrates that the value of the Work Environment (X1) and the value of Motivation (X2) affect employee performance (Y) by 69.6% while the remaining 30.4% are influenced by other variables not examined in this study. From the results of calculations using SPSS, it can be seen that the coefficient of determination of R square is 0.696. This means that the value of the Work Environment (X1) and the value of Motivation (X2) has an effect on employee performance (Y) of 69.6% while the remaining 30.4% is influenced by other variables not examined in this study.